Interna????o domiciliar: perfil dos idosos atendidos de 2006 a 2016: Gama-DF, Brasil - Caldeira, Angelita Giovana (2017)
Home care of the population in the Federal District (DF) is carried out nowadays by the Regional Centers for Home Care (NRAD's), located in the seven health regions of the Federal District, which provide care for all age groups, including the population in study - the elderly. The care takes place through a multiprofessional team, having the nurse important role in the program. The objective of this research was to describe the profile of the elderly assisted by the Home Care Program (PID) of the Regional Nucleus of Home Care (NRAD) of the South - Gama - DF health region from 2006 to 2016. This is a longitudinal study, descriptive, exploratory, quantitative approach with data from the medical records of the elderly patients admitted to the program. As a result, it was found that the female population (50.6%), married (52.5%), retired (68.8%), brown (57.5%), and the most prevalent age group is elderly people, that is, between 80 and 89 years (31.2%). The Catholic religion was the most dominant (56.9%), as well as the naturalness of the northeastern region (62.5%). The knowledge of the program was through the hospital (78.8%). The most evident reasons for hospitalization were neoplasias (43.7%), followed by Stroke (22.5) with prevalence longer than 180 days (44.3%). As diseases associated with Systemic Arterial Hypertension (SAH) and Diabetes Mellitus (DM) were the most frequent (56.2% and 25.0%). The most developed procedures were the verification of vital signs (99.3%), oximetry (88.1%), monitoring of capillary glycemia (65.6%), followed by dressing (37.5%), venous puncture (36.8%) and nasoenteric catheter, bladder of relief and delay (15.0%, 13.1% and 8.1%). At the time of admission, the main drug class in use was antihypertensive (51.8%) and 81 patients (50.6%) used 5 or more drugs. In conclusion, home hospitalization is of utmost importance to the elderly person affected by pathologies, where knowing the patient attended assists in their better follow-up, in addition to performing care that seeks to achieve the well-being of the patient in question.